The Relationship of E-WOM, Brand Ambassador to Buying Interest, and Brand Image as Mediation Variables - Diana, Nur; Juliati, Ratih; Handayanto, Eko (University of Muhammadiyah Malang, 2024)
The cosmetics industry in Indonesia continues to develop well, especially with the increasing demand for beauty products. This research was conducted to analyze and prove whether E-WOM and Brand Ambassadors influence Buying Interest with Brand Image as a mediating variable for Wardah cosmetic products at the University of Muhammadiyah Malang. This type of research uses a quantitative approach and uses primary data. Data was collected using a questionnaire of 160 respondents. The gathered data is subsequently analyzed using the Structural Equation Model - Partial Least Square (SEM-PLS) technique. The study's results prove that E-WOM, Brand Ambassador, and Brand Image significantly affect Buying Interest. In contrast, E-WOM and brand ambassadors positively and significantly affect brand image, which acts as a mediator. The Company must leverage these factors to improve its brand image and drive consumer purchasing decisions.